Analysis of long-term performance and reliability of PV modules under tropical climatic conditions in sub-Saharan. (December 2020) - Atsu, Divine; Seres, Istvan; Aghaei, Mohammadreza; Farkas, Istvan
Abstract: Reliability assessment of Photovoltaic (PV) modules is very crucial to increase the service lifetime of PV systems. This study assesses the degradation rate and reliability of PV modules operated for twelve years under the tropical climatic condition in sub-Saharan. For this purpose, various characterization techniques, namely visual inspection, infrared (IR) thermography assessment, and current-voltage (I-V) characterization, have been employed to evaluate the performance of PV modules. Moreover, the functioning of bypass diodes has been tested under partial shading situations. The results demonstrate that after twelve years of outdoor operation, the short-circuit current (Isc ) of modules have been degraded up to 16.4% with an average decrease of 11.7% compared to the nameplate values. The open-circuit voltages (Voc ) were reduced from 11.4% to 17.1% with a mean of 14.8%. The decline in Fill Factor (FF) of the modules ranges from 11.3% to 24.2%, and the losses of power output were between 34.5% and 41.4%. Moreover, the visual and thermography assessment reveals that the PV modules are severely affected by various failures such as EVA browning, cell interconnects ribbons browning and the corrosion of solder bonds. The results show that averagely, the FF is the most significant factor influencing the loss in the power output of the modules. Highlights: Degradation of PV modules under hot, humid tropical climate for 12 years assessed. PV module characteristics normalized at STC using derived translation equations. Influence of module parameters on degradation evaluated using regression analysis. The average degradation of nominal power is 3.19%/year. The combination of Isc-Voc had the most impact on the variation of nominal power.